Sustainable building materials: Ferrocement-clay roof tiles - Umar, Hj. Kassim; Kamarudin, Mohd Nor; Wan Mohd Sabki, Wan Omar; Nor Ashikin, Ahmad; Mokhzani Khair, Ishak (Universiti Tun Hussien Onn Malaysia (UTHM), 2011)
International Conference on Building Science and Engineering (ICON-BSE 2009) organized by Universiti Tun Hussien Onn Malaysia (UTHM), from 14th - 15th December 2009 at Johor Bahru, Johore, Malaysia.